2019
DOI: 10.1002/mc.23108
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 potentiates chondrosarcoma development through activation of YAP activity

Abstract: Protein arginine methyltransferase 1 (PRMT1) is identified as an oncogene implicated in various types of human cancers, while Yes‐associated protein (YAP) as a key transcriptional coactivator of the Hippo signaling plays a vital role in tissue homeostasis and tumorigenesis. To date, the underlying biological functions, prognostic values, and potential mechanisms of PRMT1 and YAP in chondrosarcoma development have not been clearly elucidated. Here, we show that upregulation of PRMT1 and YAP is significantly det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
(139 reference statements)
1
18
0
Order By: Relevance
“…Although YAP/TAZ were not investigated in these studies, it may be speculated that the observed molecular alterations affected chondrosarcoma adherence and invasion phenotypes through abrogated YAP/TAZ signaling. A recent study identified YAP nuclear accumulation as a consequence of LATS1 inactivation by protein arginine methyltransferase 1 (PRMT1) as an independent bad prognostic factor in chondrosarcoma [181]. Finally, the treatment of chondrosarcoma cells with the BET-bromodomain inhibitor JQ1 downregulated YAP/TAZ and LATS1, leading to the upregulation of cyclin-dependent kinase inhibitor 1a (CDKN1A/p21) and cell cycle arrest, senescence and apoptosis [182].…”
Section: Yap/taz In Chondrosarcomamentioning
confidence: 99%
“…Although YAP/TAZ were not investigated in these studies, it may be speculated that the observed molecular alterations affected chondrosarcoma adherence and invasion phenotypes through abrogated YAP/TAZ signaling. A recent study identified YAP nuclear accumulation as a consequence of LATS1 inactivation by protein arginine methyltransferase 1 (PRMT1) as an independent bad prognostic factor in chondrosarcoma [181]. Finally, the treatment of chondrosarcoma cells with the BET-bromodomain inhibitor JQ1 downregulated YAP/TAZ and LATS1, leading to the upregulation of cyclin-dependent kinase inhibitor 1a (CDKN1A/p21) and cell cycle arrest, senescence and apoptosis [182].…”
Section: Yap/taz In Chondrosarcomamentioning
confidence: 99%
“… 19 Clinical clinicopathological information and follow-up data were reported previously, and signed informed consent for sample collection and analysis were obtained from all patients and was in full compliance with national legislation and the ethical standards as described previously (IRB00001052-08044). 20 , 21 Human chondrosarcoma SW1353 cell line was purchased from the American Type Culture Collection (Bethesda, MD, USA) and maintained in Dulbecco’s modified Eagle medium (DMEM, Gibco, Grand Island, NY, USA) containing 10% fetal bovine serum (FBS, Gibco) and cultured in a humidified cell incubator with 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed experimental protocols have been described previously. 19 , 20 Typically, after antigen retrieval, ZNF395 (Proteintech, 13149-1-AP; 1:100) immunoreactivities were detected using the EnVision+, Peroxidase system (DAKO Diagnostics, Denmark). The slides were incubated with DAB substrate (DAKO Diagnostics, Denmark) and counterstained with hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations